1982
DOI: 10.1007/bf00239362
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of retinal inputs following striate cortex removal in adult monkey

Abstract: The morphology of the retina and central retino-recipient nuclei was studied in two monkeys that had undergone total bilateral striate cortex removal as adults. These animals had been behaviorally tested for two years after lesioning and had demonstrated significant recovery of pattern vision. Light and electron microscopy and autoradiography were done on the central retino-recipient nuclei following a monocular intravitreal injection of 3H-proline. Light microscopic analysis of retinal ganglion cell number sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 35 publications
4
30
1
Order By: Relevance
“…Even any P channel-derived inputs to hMTϩ are likely to be subject to summation and hence will likely saturate at a lower contrast than in V1. The fibers of the P pathway in particular undergo retrograde degeneration after damage to V1 (Dineen et al, 1982;Cowey et al, 1989). Surviving geniculate neurons are sparse and interspersed throughout the LGN with a mean diameter between M and P cell averages (Yukie and Iwai, 1981).…”
Section: The Relationship Between Fmri and Neurophysiology In Contrasmentioning
confidence: 99%
“…Even any P channel-derived inputs to hMTϩ are likely to be subject to summation and hence will likely saturate at a lower contrast than in V1. The fibers of the P pathway in particular undergo retrograde degeneration after damage to V1 (Dineen et al, 1982;Cowey et al, 1989). Surviving geniculate neurons are sparse and interspersed throughout the LGN with a mean diameter between M and P cell averages (Yukie and Iwai, 1981).…”
Section: The Relationship Between Fmri and Neurophysiology In Contrasmentioning
confidence: 99%
“…Earlier studies have employed surgical striate cortex lesions in adult cats and monkeys to investigate area 17/18 interactions (Donaldson and Nash, 1973), cortical blindness (Keating, 1977), visual capacity ('blind sight') remaining after the lesion (Weiskrantz and Cowey, 1970;Weiskrantz, 1978), intracortical axonal degeneration (Creutzfeldt et al, 1977), retinal degeneration (Dineen and Hendrickson, 1981), hypertrophy of dorsal lateral geniculate nucleus (dLGN) and alterations of retinal input after striate cortex lesions Dineen et al, 1982), projection patterns of surviving neurons in the dLGN (Cowey and Stoerig, 1989), and deactivation of area MT (Kaas and Krubitzer, 1992), as well as small excitotoxic striate cortex lesions to study the effects on eye movements (Newsome et al, 1985). In an earlier study we have used small acute heat lesions in the striate cortex to disclose the effects of lateral signal processing on cat single visual cortex cells (Eysel et al, 1987).…”
Section: Lesions Of the Striate Cortexmentioning
confidence: 99%
“…While anatomical (1,(12)(13)(14) and physiological (15)(16)(17) studies in monkeys have helped elucidate the neural mechanisms of the vision surviving striate cortex damage, it is still unclear to what extent the phenomenology of the residual vision in monkeys parallels that of human blindsight. Cowey and Stoerig (18) recently reported that although monkeys with striate lesions could reach for stimuli presented in the affected hemifield, they failed to distinguish between stimulus trials and blank trials in a signal-detection task.…”
mentioning
confidence: 99%